Картонный воин: роман / Андрей Ильин - Ильин Андрей Александрович (Эксмо, 2002)
Экземпляры: ФО-5 (20110413) / Инвентарный номер: 46898 / Цена: 75.00 / Сис.шифр: 84(2Рос=Рус)6 46898 / Авт.знак: И 46 / ББК: 84(2Рос=Рус)6